Genome-wide characterization of the HpHsf gene family and expression analysis under heat stress in Herpetospermum pedunculosum - Zhu, Ziwei; Liang, Haijing; Sun, Min; Yang, Yixi; Qin, Xiaoying; Zhao, Qi; Li, Rui; Tao, Yang (Frontiers in Plant Science, 2025)
IntroductionHeat shock transcription factors (Hsfs) are key regulators of plant responses to heat stress and other environmental challenges. However, the Hsf gene family of Herpetospermum pedunculosum, an alpine medicinal plant valued for its hepatoprotective properties, remains poorly characterized. Investigating the characteristics of the Hsf genes in H. pedunculosum will enhance our understanding of its thermotolerance mechanisms and provide a theoretical basis for improving its environmental adaptability.MethodsIn this study, we conducted a genome-wide identification and characterization of the Hsf gene family in H. pedunculosum. The study included analyses of protein physicochemical properties, chromosome locations, phylogenetic classification, conserved motifs, gene structures, collinearity, and cis-acting promoter elements. qRT-PCR was performed to assess the transcription levels of HpHsf genes in H. pedunculosum leaves under heat stress over a time course. Three representative HpHsfs were selected for subcellular localization analysis.ResultsHere, a total of 21 HpHsf genes were identified. Phylogenetic analysis classified the HpHsfs into three main groups (A, B, and C), consistent with classifications in other plant species. Promoter analysis revealed enrichment of stress, hormone signaling, and development-related elements. Furthermore, expression profiling under heat stress revealed significant upregulation of several HpHsfs, suggesting their involvement in heat stress response. Subcellular localization assays of three representative proteins (HpHsf3, HpHsf5, and HpHsf17) in Nicotiana benthamiana epidermal cells confirmed their nuclear localization, supporting their function as transcription factors.DiscussionThese findings provide new insights into the HpHsf gene family and lay a foundation for future functional studies on heat tolerance in alpine plants.